Berenstain Bears (The) : and the Female fullback - Berenstain, Stan (New York : Random House, 1993)
Bothered by the fact that boys and girls are treated differently in the extracurricular activities at Bear Country School, Queenie McBear decides to get some changes made.
Keywords: Sex role -- Fiction; Schools -- Fiction; Football -- Fiction; Bears -- Fiction